2019
DOI: 10.1097/iae.0000000000002137
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Preoperative External Limiting Membrane Height on Visual Prognosis in Patients Undergoing Macular Hole Surgery

Abstract: The ELM height varies widely in idiopathic macular hole. It is higher in eyes where the hole is wider and also when the hole itself is higher. For holes of less than 400 μm in width, a lower ELM height is a strong independent predictor of a good postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In contrast to the area of the cystoid cavity, the basal and minimum MH size, and the lengths of the ELM, EZ, and CIZ defects were significantly correlated with the postoperative BCVA in our results. These results are www.nature.com/scientificreports www.nature.com/scientificreports/ consistent with the findings of earlier reports 16,21 . Several studies have shown that the length of the outer retinal layer defect can be a predicting factor for the postoperative vision because they are related to the MH size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to the area of the cystoid cavity, the basal and minimum MH size, and the lengths of the ELM, EZ, and CIZ defects were significantly correlated with the postoperative BCVA in our results. These results are www.nature.com/scientificreports www.nature.com/scientificreports/ consistent with the findings of earlier reports 16,21 . Several studies have shown that the length of the outer retinal layer defect can be a predicting factor for the postoperative vision because they are related to the MH size.…”
Section: Discussionsupporting
confidence: 92%
“…There have been many reports describing the relationship between the BCVA and the preoperative morphology determined by OCT in eyes with MH, e.g. the basal and minimum MH size 8,9,15 , the ELM height 16 , and the maximum retinal thickness 10 . Our results showed that the area of the cystoid cavities was correlated with the preoperative BCVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metamorphopsia in patients is the perception deviation of the horizontal or vertical line, and it sometimes may appear before the clinical manifestation of macular disease [3338]. Patients may sometimes consider metamorphopsia as an unstable condition of vision instead of precise deformations of objects, and they focus better with slightly unconscious eye movements.…”
Section: Metamorphopsiamentioning
confidence: 99%
“…To evaluate metamorphopsia, many functional examinations can be conducted, such as the Amsler grid and the mobile handheld home surveillance devices [57]. The Amsler grid [34, 37, 38, 58] was the first functional test to be evaluated for visual distortion. This test enables simple and fast qualitative assessment of changes in the visual function in the field of view of central 10°, which might appear prior to certain macular diseases or together with the development of these diseases.…”
Section: Metamorphopsiamentioning
confidence: 99%